PENGARUH HARGA DAN BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN PADA PT. AGUNG TOYOTA CABANG COKROAMINOTO DENPASAR - Ni Ketut Narti; Ni Ketut Lasmini; Lily Marheni; I Putu Mico Jayadinatha (Forum Manajemen STIMI Handayani Denpasar, 2021)
Price and brand image have an important role in purchasing decisions. This study aims to examine and analyze the effect of price and brand image partially and simultaneously on the purchase decision of Toyota Avanza at PT. Agung Toyota Cokrominoto Denpasar Branch. The benefit of this research is to provide information on the effect of price and brand image partially and simultaneously on the purchase decision of Toyota Avanza at PT. Agung Cokroaminoto Denpasar Branch This research is a quantitative study using a sample of 90 people who know about prices and brand image at PT. Agung Toyota Cokroaminoto Denpasar Branch for data collection in this study using a questionnaire distributed via the internet. In this study using a non probability sampling method, namely purposive sampling. The analysis technique used is multiple linear regression analysis, analyzed using the SPSS version 25 program for windows. The results of this study indicate that (1) price has a positive and significant effect on purchasing decisions of Toyota Avanza cars at PT. Agung Toyota Cokroaminoto Denpasar Branch; (2) brand image has a positive and significant effect on purchasing decisions of Toyota Avanza cars at PT. Agung Toyota Cokroaminoto Denpasar; (3) price and brand image together significantly influence the purchase decision of Toyota Avanza cars at PT. Agung Toyota Cokroaminoto Denpasar Branch.